Estudo do efeito nefroprotetor do extrato alcoólico de própolis vermelha em um modelo de lesão renal aguda por isquemia/reperfusão em ratos - Costa, Marcus Felipe Bezerra da (2013)
Kidney disease remains a public health problem worldwide, where there is an increase in the number of incidence of Acute Kidney Injury (AKI) in hospitalized patients. The AKI is characterized by an abrupt decrease in renal function, resulting in the inability of the kidneys to perform it´s basics functions. The Ischemia/Reperfusion (I/R) injury can be defined as all changes resulting from the deprivation and the re-establishment of the oxygen supply to tissues and organs. It is a complex process that results in the production of reactive oxygen species (ROS) and oxidative stress damage. The Brazilian Red Propolis is a complex mixture collected and produced by Apis mellifera bees, and seems to be promising in this context, attenuating the oxidative and nephrotoxic effect in the kidney. This experimental study aims to replicate and standardize a framework of AKI by Ischemia/reperfusion (I/R) in rats, and analyze the possible protective renal effects of Red Propolis Alcohol Extract (RPAE) at a dose of 150mg/kg on markers and pathological variables. Wistar rats, adult males, were divided into 4 groups, using an induction and treatment regimen. We evaluated biochemical parameters indicative of renal function (creatinine, urea, creatinine clearance) tubular function (FENa+ and FEK+), oxidative profile through MDA (malondialdehyde) and activity of antioxidant enzyme GSH, in addition to histological analysis and immunohistochemistry. The RPAE significantly altered almost all parameters investigated. The results demonstrated the protective effect of the extract in the dose used against the nephrotoxicity: decreased serum levels of creatinine (1.8 ± 0.5 vs 2,7±0,9) and urea (181.1 ± 65.6 vs 274,3±91,81), reversed the increase in FENa+ (0,58±0,30 vs 1,03±0,39) and FEK+ (64,74±52,44 vs 134,4±54,94), reversed the decrease of creatinine clearance (0,41±0,14 vs 0,073±0,048), decreased MDA levels (90,22±20,82 vs 133,9±23,36) and increased GSH (1784±297,4 vs 1267±229,5), decreased the rate of acute tubular necrosis (2,0±0,7 vs 3,6±0,5), increased the expression of eNOS (2,2±0,4 vs 0,6±0,5) and Heme-oxygenase (2,6±0,5 vs 1,4±0,5). Therefore, occurred protection of renal function, protection of the tubular damage and oxidative stress. These results describe for the first time the effect of Red Propolis on a model of AKI induced by I/R, suggesting the protective effect of the extract against this type of injury.